2022
DOI: 10.1029/2022gh000603
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide and Regional PM2.5‐Related Air Quality Health Benefits From the Removal of Energy‐Related Emissions in the United States

Abstract: There is a clean energy transition underway in the United States (US). Since 2015, about a dozen states and the District of Columbia (DC) and Puerto Rico have set targets requiring that all their electricity production come from clean or carbon-free sources, in many cases by between 2040 and 2050, and other states have set similar non-binding goals (Paulos et al., 2021). Such ambitious clean energy proposals are most common in the electric power sector, but others focus on transportation. In 2020, California s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 50 publications
(142 reference statements)
0
10
0
1
Order By: Relevance
“…This scenario leads to air quality improvement in Pennsylvania, Ohio, Indiana, and Illinois (figure 2(b)), states in the Rust Belt with high levels of coal combustion for electricity generation. Other studies have also found this region to have high cobenefits from clean electricity (Millstein et al 2017, Abel et al 2018, Buonocore et al 2019, Mailloux et al 2022. The northern half of the U.S. has a larger White population, including the states located in the Rust Belt (figure 2(d)).…”
Section: Evaluation Of Distributive Ejmentioning
confidence: 84%
See 1 more Smart Citation
“…This scenario leads to air quality improvement in Pennsylvania, Ohio, Indiana, and Illinois (figure 2(b)), states in the Rust Belt with high levels of coal combustion for electricity generation. Other studies have also found this region to have high cobenefits from clean electricity (Millstein et al 2017, Abel et al 2018, Buonocore et al 2019, Mailloux et al 2022. The northern half of the U.S. has a larger White population, including the states located in the Rust Belt (figure 2(d)).…”
Section: Evaluation Of Distributive Ejmentioning
confidence: 84%
“…While the county-scale of COBRA limits urban-scale analysis, the resolution may be compared with county-scale demographic data, consistent with previous nationwide EJ research (Miranda et al 2011, Rowangould 2013, Clark et al 2014. COBRA has been used to quantify air quality co-benefits in research applications at various scales and policy evaluations: (Mailloux et al 2022). COBRA has also previously been used to investigate PM 2.5 exposure to socially vulnerable populations from prescribed fire smoke, which includes race/ethnicity, socioeconomic status, and other demographics (Afrin and Garcia-Menendez 2021).…”
Section: Methodsmentioning
confidence: 99%
“…[43] The death toll is especially high in China, India, and other newly industrializing countries, but air pollution causes hundreds of thousands of deaths in high-income countries, too, including 38 000 per year in the United States according to WHO estimates, [44] and possibly more. [45] The central objection to carbon pricing voiced by EJ advocates has been that it could widen pollution exposure disparities. Carbon pricing lets polluters decide whether, where, and how to curtail emissions or choose instead to pay the price.…”
Section: Principle #2: Protect the Air: An Ej Mandate For Emissions O...mentioning
confidence: 99%
“…[ 43 ] The death toll is especially high in China, India, and other newly industrializing countries, but air pollution causes hundreds of thousands of deaths in high‐income countries, too, including 38 000 per year in the United States according to WHO estimates, [ 44 ] and possibly more. [ 45 ]…”
Section: Principle #2: Protect the Air: An Ej Mandate For Emissions O...mentioning
confidence: 99%
“…Non-accidental mortality attributable to specified changes in CRP and PDSI are estimated using the formulas and parameters developed by Burnett et al (2018). The concentration-response function published in that work is formulated using results from 41 cohorts across 16 countries and has been used previously in U.S.-specific health effects research (e.g., Mailloux et al, 2022). The population-wide hazard ratio, predicted annual average fine particulate matter concentrations, and baseline non-accidental county mortality incidence counts were used to estimate excess mortality in three counterfactual scenarios; Scenario 1 (all CRP removed, i.e., all available farmland is under cultivation); Scenario 2 (a decrease of 4 on the PDSI scale); and Scenario 3 (a combination of Scenarios 1 and 2).…”
Section: Quantifying the Air Quality Impacts Of Crp And Droughtmentioning
confidence: 99%